Ultra-processing markers are more prevalent in plant-based meat products as compared to their meat-based counterparts in a German food market analysis - Kemja-Maria Metz; Nathalie Judith Neumann; Mathias Fasshauer (Public Health Nutrition, 2023)
Abstract